2021
DOI: 10.1186/s40798-021-00347-1
|View full text |Cite
|
Sign up to set email alerts
|

Weaving Lines of Inquiry: Promoting Transdisciplinarity as a Distinctive Way of Undertaking Sport Science Research

Abstract: The promotion of inter- and multidisciplinarity — broadly drawing on other disciplines to help collaboratively answer important questions to the field — has been an important goal for many professional development organisations, universities, and research institutes in sport science. While welcoming collaboration, this opinion piece discusses the value of transdisciplinary research for sports science. The reason for this is that inter- and multidisciplinary research are still bound by disciplinary convention —… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
(70 reference statements)
0
21
0
Order By: Relevance
“…However, a distinctive feature of transdisciplinarity is weaving lines of inquiry that may have remained isolated from one another due to disciplinary traditions and perceived boundaries (Woods et al, 2021a ). In that spirit, we find a generative strand of conceptual alignment between socio-cognitive and ecological notions of values.…”
Section: An Atde Needs To Be Sociomaterials and Coupled To Affordance...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, a distinctive feature of transdisciplinarity is weaving lines of inquiry that may have remained isolated from one another due to disciplinary traditions and perceived boundaries (Woods et al, 2021a ). In that spirit, we find a generative strand of conceptual alignment between socio-cognitive and ecological notions of values.…”
Section: An Atde Needs To Be Sociomaterials and Coupled To Affordance...mentioning
confidence: 99%
“…It has to be noted that knowledge about the environment is associated with the traditional modes of communication used by coaches, trainers, and practitioners in most sports organizations. Thus, coach education programmes are deeply infused with pedagogical methodologies dominated by the transmission of abstract knowledge about the performance environment (Vaughan et al, 2021 ; Woods et al, 2021a ).…”
Section: Football In Stockholm: the Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This uncertainty is what makes us attentive, actively listening to what the other has to share with us so that we can find ways to join with their experiences and carry the conversation on. Elsewhere, it has been suggested that this type of discourse is to take up with research as a journey, not a destination, where determinate pre-planning gives way to a progressively attuned responsiveness that sees the researcher selectively follow, and weave together, emergent lines of inquiry [ 40 ]. This is an approach to scientific inquiry that is undergone together , in which experiments are done with , not on , and observations are not about , but with .…”
Section: Entering Into a Good Conversationmentioning
confidence: 99%
“…To move away from reductionist and siloed practices, researchers [ 28 , 41 , 42 ] have conceptualised a transdisciplinary framework for sport scientist and coach integration called a department of methodology (DoM). At the core of a DoM is a view of transdisciplinarity that (re)positions a collective of practitioners as an integrated, inquiry-based unit collaboratively solving development- and performance-based problems [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%